Financing the Implementation of National and Regional Projects: Problems and sustainable Development Directions - K. N. Samkov (Финансы: теория и практика)
Regional projects and programs are intended to become the main mechanism for achieving national development goals in territorial entities. The aim of the article is to analyze the problems of project implementation and program approaches at the level of the constituent entities of the Russian Federation, as well as to develop proposals for their development. The methodological basis of the study is the regulatory legal acts of the federal and regional levels, scientific (foreign and domestic) literature in the field of economics and public finance, official statistical information, empirical data regarding the results and progress of the implementation of regional projects and state programs of the constituent entities of the Russian Federation. The author uses the method of system analysis. The article analyzes the conceptual foundations of project management in the public sector, foreign and domestic research on this issue, examples of program implementation abroad, establishes the role of regional projects and state programs in the budget system of the Russian Federation, their relationship, identifies the main problems of their financing, considers examples of direct implementation of projects and programs, and suggests directions for their development. In the course of the study, the distortion of the initially inherent meanings of the implementation of the project approach is proved, first of all, in determining the goal setting, providing sufficient mechanisms for its achievement and financing. It is established that the state programs at present actually represent documents of planning of budget appropriations in implicit interrelation with the main directions of activity of authorities. It is concluded that it is necessary to clarify the current project and program methodology, which will allow the regions not only to engage in the implementation of federal projects but also to initiate them according to the priorities of socio-economic policy and the characteristics of the region. The author also proposes to develop regional projects as financial institutions. For this, it is necessary to clarify the budget legislation to ensure the possibility of actual planning of expenditure obligations within the framework of the design of projects. The prospects for further research are to develop a model for evaluating the effectiveness of the design and implementation of regional projects and state programs, and its further testing on specific programs of the constituent entities of the Russian Federation.